PERBEDAAN REAKSI PASAR ATAS PENGUMUMAN PEMECAHAN SAHAM PADA LQ45 DAN NON LQ45 - Meylita P, Hanny; Yasa, Gerianta Wirawan (Jurnal Ilmiah Akuntansi dan Bisnis, 2015)
The stock split is one form of corporate action conducted by the company to increase the liquidity of the stock. This activity is usually do when the stock price is overvalued or performed by companies that have low liquidity. Interestingly, LQ45 companies known to have a high level of liquidity in the Indonesia Stock Exchange is still do stock split. This study aims to determine the market reaction to the LQ45 company and nonLQ45 the stock split to see whether there is a difference of abnormal return during the event window. The period of observation made in this study is 7 days. Sampling method is purposive sampling, and its found 9 LQ45 company and 37 nonLQ45 company listed on the Indonesia Stock Exchange. Return expectations in this study calculated with mean adjusted model. The hypothesis was tested using One Sample t-test, and Independent t-test. The results statistical hypothesis testing showed that the events on LQ45 and non LQ45 company gets a reaction from the market during the event window.
Keywords: stock split; abnormal return; market reaction; signaling theory